On the optimal user grouping in NOMA system technology - Masaracchia, Antonino; Ha, Dac-Binh; Le, Ngoc-Phuc (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2019)
This paper provides a state-of-art analysis of the most relevant studies on optimal user-aggregation strategies for non-orthogonal multiple access (NOMA) technology. The main ideas behind are i) to highlight how, in addition to the adoption of an optimal power allocation scheme, an optimal user-aggregation strategy represents an important key factor for improving NOMA system performance, and ii) to provide an exhaustive survey of the most relevant studies which can serve as useful starting point for the definition of new channel state-aware user-aggregation strategies for NOMA systems which, at the time of writing, represents a research field that still remains to be investigated more in depth. A detailed and complete analysis, which permits to point out the need to guarantee a certain relationship between users’ channel gain, is provided for each cited work.
Keywords: Algorithms and Protocols; Communication networks; Intelligent systems; Optimization; Survey and review